Leveraging research infrastructure co-location to evaluate constraints on terrestrial carbon cycling in northern European forests - Martyn N. Futter; Thomas Dirnböck; Martin Forsius; Jaana K. Bäck; Nathalie Cools; Eugenio Diaz-Pines; Jan Dick; Veronika Gaube; Lauren M. Gillespie; Lars Högbom; Hjalmar Laudon; Michael Mirtl; et al. (Ambio, 2023)
Integrated long-term, in-situ observations are needed to document ongoing environmental change, to “ground-truth” remote sensing and model outputs and to predict future Earth system behaviour. The scientific and societal value of in-situ observations increases with site representativeness, temporal duration, number of parameters measured and comparability within and across sites. Research Infrastructures (RIs) can support harmonised, cross-site data collection, curation and publication. Integrating RI networks through site co-location and standardised observation methods can help answers three questions about the terrestrial carbon sink: (i) What are present and future carbon sequestration rates in northern European forests? (ii) How are these rates controlled? (iii) Why do the observed patterns exist? Here, we present a conceptual model for RI co-location and highlight potential insights into the terrestrial carbon sink achievable when long-term in-situ Earth observation sites participate in multiple RI networks (e.g., ICOS and eLTER). Finally, we offer recommendations to promote RI co-location.